PENGARUH KOMBINASI TWISTED TAPE SWIRL FLAT WIRE COIL TERHADAP PERFORMA DOUBLE PIPE HEAT EXCHANGER PADA SISTEM SOLAR WATER HEATER - Rif’atus Sholihah; Arrad Ghani afitra (IST AKPRIND Yogyakarta, 2018)
A solar water heater is an energy storage by using heat energy of sun for heating fluid. Solar water heater has a modification to improve effectiveness, by adding double pipe heat exchanger type u-tube. The working fluid in double pipe heat exchanger consists of water as coolant in outer pipe and SAE 10 oil as a heater in inner pipe and flow occurs by counter flow. To improve the performance double pipe heat exchangers, it was using twisted tape and using SAE 10 oil for working fluid. The experiment was conducted experimentally by varying swirl and flat twisted tape combinations and adding wire coil to increase heat transfer. Variations used are swirl-flat-swirl (s-f-s) twisted tape wire coil, flat-swirl-flat (f-s-f) twisted tape wire coil and plain as a basic reference. Retrieval of data was carried out from 10:00 a.m to 3:00 p.m, the data consist of intensity sunlight radiation, temperature inlet and outlet water fluid, temperature inlet and outlet oil fluid. From the results of testing, the plain variation high effectiveness is 0,32, NTU is 0,38 at 2:00 p.m with the intensity of solar radiation is 515, twisted tape s-f-s with wire coil high effectiveness is 0,43, NTU is 0.56 at 11:00 a.m with a sun intensity is 786, and twisted f-s-f tape with wire coil high effectiveness is 0,4, NTU is 0.52 at 1:00 p.m. with the intensity the sun is 751.